Scribes and scribalism - Leuchter, Mark (The Hebrew Bible in Social Perspective Ser., 2020)
Cover -- Title -- Copyright -- Contents -- Abbreviations -- Notes on Contributors -- Series Editor's Preface -- Introduction: The Scholarly Context for the Study of Scribes and Scribalism / Mark Leuchter -- Part One Praxis and Materiality -- Influential Inscriptions: Resituating Scribal Activity during the Iron I-IIA Transition / Sarah Malena -- The Media and Materiality of Southern Levantine Inscriptions: Production and Reception Contexts / Madah Richey -- Scribes and Scribalism in Archaic Crete / Anselm C. Hagedorn -- Part Two Power and Status -- Scribes, Schools and Ideological Conflict in Ancient Israel and Judah / Brian Rainey -- Ecclesiastes and the Problem of Transmission in Biblical Literature / Jacqueline Vayntrub -- Textualization and the Transformation of Biblical Prophecy / Heath D. Dewrell -- Reorientation in Responsibility of Levites Taking Care of the Ark: The Levites' Role in Samuel-Kings in Relation to Deuteronomistic Expressions Concerning Interpretation of the Law / Antje Labahn -- Part Three Between Ideology and Authority -- Writing in Three Dimensions: Scribal Activity and Spaces in Jewish Antiquity / Laura Carlson Hasler -- Rejecting "Patriarchy": Reflections on Feminism, Biblical Scholarship, and Social Perspective / Shawna Dolansky -- Bibliography -- Index of References -- Index of Authors.